The Social Media Marketing Strategies of Tourism Regions and Enterprises - Kachniewska, Magdalena (Studia Oeconomica Posnaniensia, 2017)
The paper seeks to discuss the basis for a modern social media marketing strategy, including a new communication paradigm and new ways of database construction. It is based on the literature research (including Internet publications on tourism trends and e-consumer journeys) and the case studies of tourism enterprises/organizations/regions modern marketing strategies. The paper identifies the marketing gap illustrating the difference between the traditional marketing tools and the most appropriate SM marketing techniques. The results of the analysis should be discussed further, as the case study analysis does not ensure the representativeness of research; however it helps to illustrate the major marketing trends. The analysis of Western European organizations needs a critical approach due to the cultural differences (mainly of the different digital literacy of western and eastern European societies). The limitations do not seem to be accurate in the case of younger generation (Gen Y). This paper will be of immense value to tourism industry leaders, formulating the basis for their SM marketing strategies. It should also enhance the use of new media effectiveness indicators. The paper contributes to the knowledge of tourism SM marketing strategies being a guide for tourism policy planners and managers. It is the first publication in Poland on the marketing gap between old and new media.